Defects in mitochondrial fatty acid synthesis result in failure of multiple aspects of mitochondrial biogenesis in Saccharomyces cerevisiae. Issue 4 (10th October 2013) - Kursu, V. A. Samuli; Pietikäinen, Laura P.; Fontanesi, Flavia; Aaltonen, Mari J.; Suomi, Fumi; Raghavan Nair, Remya; Schonauer, Melissa S.; Dieckmann, Carol L.; Barrientos, Antoni; Hiltunen, J. Kalervo; Kastaniotis, Alexander J.
Summary: Mitochondrial fatty acid synthesis (mtFAS) shares acetyl‐CoA with the Krebs cycle as a common substrate and is required for the production of octanoic acid (C8) precursors of lipoic acid (LA) in mitochondria. MtFAS is a conserved pathway essential for respiration. In a genetic screen in Saccharomyces cerevisiae designed to further elucidate the physiological role of mtFAS, we isolated mutants with defects in mitochondrial post‐translational gene expression processes, indicating a novel link to mitochondrial gene expression and respiratory chain biogenesis. In our ensuing analysis, we show that mtFAS, but not lipoylation per se, is required for respiratory competence. We demonstrate that mtFAS is required for mRNA splicing, mitochondrial translation and respiratory complex assembly, and provide evidence that not LA per se, but fatty acids longer than C8 play a role in these processes. We also show that mtFAS‐ and LA‐deficient strains suffer from a mild haem deficiency that may contribute to the respiratory complex assembly defect. Based on our data and previously published information, we propose a model implicating mtFAS as a sensor for mitochondrial acetyl‐CoA availability and a co‐ordinator of nuclear and mitochondrial gene expression by adapting the mitochondrial compartment to changes in the metabolic status of the cell.